Efficacy of intermittent versus continuous phototherapy in the treatment of unconjugated hyperbilirubinemia in newborns - حسن, علي; هلا يني , (Latakia University Journal -Medical Sciences Series, 2024)
Background: Jaundice in newborns is a common disease and an important reason for hospitalization and medical intervention. Phototherapy is the first and most widely used in medical treatment of jaundice. Current studies refer to use intermittent rather than continuous phototherapy to reduce the side effects of phototherapy. Objectives: To study the effectiveness of intermittent phototherapy versus continuous in the treatment of unconjugated hyperbilirubinemia in newborns. Methods: An analytical observational study involved 63 neonates at Tishreen University Hospital Latakia during the period from August 2022 to September 2023. The patients were divided into two groups: group A received intermittent phototherapy (2 hours on/ 1 hours off) and group B received continuous phototherapy for 12 hours. Total serum bilirubin values were measured at hospitalization and after 6 and 12 hours of phototherapy Results:The mean of total serum bilirubin at admission was 16.6±1.33 mg/dl for the intermittent group A and 16.8±1.34 mg/dl for the continuous group B. The TSB mean after 6 and 12 hours for the intermittent group A was 15.7±0.4 mg/dl, 13.7±1.33 mg/dl and 15.5±0.7 mg/dl, 13.5±1.22 mg/dl for the continuous group B, respectively. There was no any significant difference between the two groups regarding TSB (P-value˃5%). Conclusion: Intermittent phototherapy is as effectives as continuous one in the treatment of unconjugated hyperbilirubinemia in newborns.